On Book Culture of Czech and Moravian Jews in the Middle Ages - Polakovič, Daniel (Bohemica Olomucensia, 2013)
The contribution examines and contextualizes sources for exploration of book culture of medieval Jews in the Czech lands. If offers an overview of preserved works and their fragments and focuses further on the Canaanite glosses offering a unique testimony to the medieval importance of Czech, especially Prague Jewish community.